Physiological Responses of Broiler Chickens to Quantitative Water Restrictions: Haematology and Serum Biochemistry - Iheukwumere, F.C.; Herbert, U. (International Journal of Poultry Science, 2003)
The effect of water restriction on haematology and serum biochemistry of broiler chickens was investigated. A total of ninety six 4-week old Anak broiler birds were used for this study. The birds were divided into 4 treatment groups and within each group, replicated three times at 8 birds per replicate. Different quantities of water were fed to the birds as treatments, that is, ad libitum (To), 3.2 liters (T1), 2.2 liters (T2), 1.2 liters (T3) per day in a completely randomized design (CRD) experiment. The results show that the haematological values were significantly influenced (P<0.05) by severity of water restrictions. However, broilers on T3 (1.2 liters of water restriction) showed a higher mean value for white blood cell (WBC), which differed, significantly from To (control) and T1 (3.2 liters of water restrictions). The mean values of the chemical constituents (Na+, K+, Ca++, Cl-, HCO3-) in the sera of the broiler chickens were significantly (P<0.05) influenced by severity of water restrictions. There was no significant difference (P>0.05) for Alkaline phosphatase and Aspartate transaminase enzyme activity but Alanine transaminase showed significant differences (P<0.05) between the treatments. Total protein albumin showed significant (P<0.05) difference between the treatments but serum globulin did not differ significantly (P>0.05) between the treatments.